Culture Shock In Intercultural Communication (Qualitative Descriptive Study About Culture Shock For Foreign Students From Palestine And Thailand Countries In Muhammadiyah University Of Surakarta) - Noviana, Indah (2014)
This research aims to describe the communication is obstacles and the stages of culture shock that faced by the University of Muhammadiyah Surakarta (UMS's) students who are from Palestine and Thailand countries. The method uses qualitative descriptive by using technical data collection with semi-structural of technique interview and to check the data validity with source triangulation. Results of research that the students from Palestine and Thailand countries didn't know about living in Indonesia especially in UMS's environment before they come to Indonesia, after living in Surakarta, they can understand the local culture from time by time. The obstacles of communication and the stages of the culture shock in faced by foreign studentsthat are from them self and society. Most of foreign students could minimize the culture shock by using social support as friends, family or community, but some foreign students the influence of ethnic differences and the time in overcoming culture shock. Where as in the implementation of handling culture shock that can adapt quickly and others take a long time.